IMPROVEMENT THROUGH EMOTIONAL INTELLIGENCE GROUP COUNSELING SERVICES WITH STUDENTS PSYCHOANALYTIC APPROACH SMP STATE 11 PADANGSIDIMPUAN - KHAIRUL AMRI (Ristekdik : Jurnal Bimbingan dan Konseling, 2018)
The study was based on the problems that still lack emotional intelligence of students. The study goal was to describe the emotional intelligence of students before and after the group gave guidance services, with the psychoanalytic approach. The method used in this research is True experimental design with shapes pretest-posttest control group design. With a sample of experimental class is class VII-1 by 10 students and the control class is class VII-2 as many as 10 students so as the total sample of 20 students. Data collection techniques in this research using questionnaires, distributing questionnaires aim is to obtain the specific information requested. Data were analyzed with the help of Excel or SPSS (Statistical Product and Service Solution) version 20. From the results of the implementation is done, a significant increase is mainly posttest experiment. The findings in the experimental group and the control group there were significant increases between posttest results and posttest control experiment. The average child's emotional intelligence variable Pre-Test and Post-Test class in looking for the experimental and control average. In the experimental group pre-test value is obtained at 91.7 and the control class values obtained pre-test of 120.5. While the results of the post-test experimental class obtained a value of 87.6 and a post-test values at control class is 107.0 is seen a very significant difference. The conclusion of this study the results of the processing of the data, indicate that the implementation of guidance services group with psychoanalytic approach can improve the emotional intelligence of students of SMPN 11 Padangsidimpuan. Keywords: Increasing Emotional Intelligence, Guidance Services Group With Psychoanalytic Approach